Acquisition and completion of pregnant woman's medical booklet in four populational-based surveys - Tatiane Nogueira Gonzalez; Juraci Almeida Cesar
Abstract Objectives: to measure the prevalence of acquiring and evaluating the level of completion of the pregnant women's medical booklet on the occasion of childbirth in Rio Grande, Brazil. Methods: this is a cross-sectional study including all puerperals residing in this municipality in 2007, 2010, 2013 and 2016. The mothers were interviewed at the only two local maternities up to 48 hours after childbirth. The data from the pregnant woman's medical booklet were copied on a standard form. The chi-square test was used to compare proportions. Results: 10,242 pregnant women were included in this study. Of these, 54.8% (CI95%=53.8%-55.7%) had their pregnant woman's medical booklet with them at the time of admission. The completion pattern of the pregnant woman's medical booklet is divided into three groups, namely: with at least 95%: date of the last consultation visit, maternal height and blood pressure verification, uterine height, cardio-fetal heart rate and the Rh factor; 85% or more: date of the last menstruation, qualitative urine test, VDRL and HIV; and less than 30%: performance of clinical breast examination and cytopathology of the uterine cervix. In the private sector, the acquisition of the pregnant woman's medical booklet was 41% lower than at the public sector (62% vs. 44%). Conclusions: the use of the pregnant woman's medical booklet and its completion were lower than expected on several items. Local managers need to work together with the health professionals and these health professionals should work with the mothers to promote the full use of this essential document for the maternal and child's health.